A taxonomic review of the Golden-green Woodpecker, Piculus chrysochloros (Aves: Picidae) reveals the existence of six valid taxa - Del-Rio, Glaucia; Silveira, Luís Fábio; Cavarzere, Vagner; Rêgo, Marco Antonio (Zootaxa, 2013)
Piculus chrysochloros (Vieillot 1818) is a species of woodpecker that ranges from Argentina to Panama, occurring in lowland forests as well as Cerrado, Caatinga and Chaco vegetation. Currently, nine subspecies are accepted, but no study has evaluated individual variation within populations, so the status of these taxa remains uncertain. Here we review the taxonomy and distribution of this species, based on morphological and morphometric data from 267 specimens deposited in ornithological collections. Our results suggest the existence of six unambiguous taxonomic units that can be treated as phylogenetic species: Piculus xanthochloros (Sclater & Salvin 1875), from northwestern South America; Piculus capistratus (Malherbe 1862), from northern Amazonia west to the Branco River; Piculus laemostictus Todd 1937, from southern Amazonia; Piculus chrysochloros (Vieillot 1818), from the Cerrado, Caatinga and Chaco; Piculus paraensis (Snethlage 1907) from the Belém Center of Endemism; and Piculus polyzonus (Valenciennes 1826) from the Atlantic Forest. Both Brazilian endemics (P. polyzonus and P. paraensis) are threatened due to habitat loss. In addition, we found one undescribed form from the Tapajós-Tocantins interfluve, now under study, that may prove to be a valid species once more specimens and other data become available.